26 years left behind: a historical and predictive analysis of electronic business research - Cadirci, Tugce Ozansoy; Gungor, Aysegul Sagkaya (SPRINGER, 2021)
This article reviews 26 years (1994-2020) of research on electronic business published in reputable journals of the field. The basic aim behind this study is to define the growth potential of electronic business and marketing as a theoretical field and provide insights on past, present, and future scientific production in the field. By using bibliometrics and topic modeling techniques, annual scientific production and growth, latent topic structures, and trends by years, information on total citations and networks were examined. While the authors defined the research orientations by uncovering the main topics associated with electronic business, they created an understanding of the possible future research directions of fourteen topics discovered. The results show that, while the transaction-focused publications prevailed in the early years of electronic business and marketing journals, from the mid2000s, the focus has shifted towards marketing-focused publications. Moreover, to understand the main orientations in the field, the authors conducted a citation analysis to define the most influential topics published in the journals. The article also provides information on the most influential researchers in the field.
Keywords: Topic modeling; Historical analysis; Electronic business; Latent dirichlet allocation; OF-CONSUMER-RESEARCH; Business & Economics